Collaboration as a Means of Technological Development and Learning: Demonstrated by a Case Study within the Biotech Industry - Brecht, Daniela (2008)
Over the last decade the biotech industry has been facing an increasingly turbulent environment (Howseman, 2006). In recent years, the technological focus has shifted dramatically (Williams, 2007). Biotechnology companies have responded to these conditions by forming a wide range of collaborative partnerships, which may vary by underlying rationale, time frame, and form. The number of alliances within the Biotech sector in 2007 more than doubled compared to 2005, with a clear dominance of pharma-biotech deals (Ernst& Young, 2007).